2019
DOI: 10.12669/pjms.35.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Immature to total neutrophil ratio as an early indicator of early neonatal sepsis

Abstract: Background & Objectives: Neonatal septicemia is responsible for 1.5 to 2.0 million deaths/year in the under developed countries of the world. Pakistan is number three among these countries and accounts for 7% of global neonatal deaths. The objective of the study was to determine the role of simple hematological parameter, immature to total neutrophil ratio (I/T ratio) in diagnosing early onset neonatal bacterial infection. Methods: A descriptive cross-sectional study was conducted in Neonatal Intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Immature to total neutrophil ratio (I/T ratio) has been proposed as a marker for early detection of neonatal sepsis, in which an increase in I/T ratio is a reasonable predictor of positive blood culture (sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of I/T ratio were 76.47%, 83.82%, 54.16%, and 93.44%, respectively), especially when used in conjunction with C-reactive protein (CRP) values. 31 Our TriNetX data therefore suggests that NAS-diagnosed neonates may be at an increased risk for infection. There were no statistically significant differences between other cell populations or findings (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Immature to total neutrophil ratio (I/T ratio) has been proposed as a marker for early detection of neonatal sepsis, in which an increase in I/T ratio is a reasonable predictor of positive blood culture (sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of I/T ratio were 76.47%, 83.82%, 54.16%, and 93.44%, respectively), especially when used in conjunction with C-reactive protein (CRP) values. 31 Our TriNetX data therefore suggests that NAS-diagnosed neonates may be at an increased risk for infection. There were no statistically significant differences between other cell populations or findings (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Sepsis may lead to anaemia due to malfunction of the bone marrow or bleeding (petechiae, purpura, seeping) and haemorrhage [20] In this research, the positive CRP was 57 instances (95%), compared to 16 cases (40%) of the negative culture group. Similarly, [11] noted that CRP in positive blood cultured patients is significantly greater than in those with negative cultures (p<0.001). Among the 188 neonates hospitalised with suspected EONS, in 160 [85.1 percent] instances the CRP level was positive [>6 mg/L];…”
Section: Benhamentioning
confidence: 86%
“…And, in [10] research of 115 children, all sepsis/baacteremia patients showed substantially increased WBC levels (17.94 ± 10.04 ± 109/L vs 10.42, respectively ± 4.21 ± 109/L; p < 0.001), and the number of neutrophils (10.93 ± 8.03 ± 109/L versus 5.08 ± 3.42 ± 109/L; p < 0.001). In addition [11] patients with confirmed sepsis were found to have WBC greater than 26000 compared to negative WBC diagnosis <15500.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study, the I/T ratio showed a sensitivity of 78.8% and a specificity of 92% in the diagnosis of EOS. However, Saboohi et al (52) reported that the I/T ratio showed a sensitivity of 76.47% and a specificity of 83.82% in the diagnosis of EOS.…”
Section: Discussionmentioning
confidence: 98%